Historiography of the Study of Animal Husbandry of The Lower Amudarya (1873-1941) - Khorezmiy Abdikarimov (Zien Journals, 2022)
In this article, we have done a lot of work on the development of animal husbandry in the Amudarya region and its coverage in historical sources. As a result, we have the information we need for the future, and we have brought this to the appearance of the article.
Keywords: animal husbandry; pastoralism; totalitarian regime; analysis of historical events